Investor relations as a company image component - Sobczak-Spasiuk, Aleksandra (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
Purpose: The purpose of this article is to describe what organizational image means and identify Investor Relations (IR) as an important component that shapes organizational image. Design/methodology/approach: Literature review of organizational science regarding image building and investor relations. Findings: A company’s ability to make a profit is crucial for investors, however, their decisions taken in the present, to buy, hold or sell company shares relate to the future and expected benefits associated with the investment. The share prices do not only reflect a company’s financial situation. Thus, information itself is not sufficient – the obligation imposed on companies is to report their financial results. A broader context that gives the opportunity to evaluate the company is needed. Therefore, listed companies within IR need to provide information and take actions to shape the current picture of a company, due to which they are able to strive for the outstanding and strategically defined image to attract investors and other stakeholders. In other words, through transparent and planned activities create an image that influences appropriate investment decisions. Research limitations/implications: The paper is limited to the review of the literature on investor relations and image creation from PR and management perspective and refers to companies listed on the Warsaw Stock Exchange. Original value: The paper describes a strategic value of investor relations which due to planned communication impacts on how the company is perceived. Furthermore, the author argues that transparent and voluntary activities increase the competitiveness of company shares.